Advocacy / David Ross. - Ross, David, 1943-2009 (Cambridge University Press, 2007)
Advocacy, first published in 2007, explains how to win cases in court. Focusing on the techniques and methods of successful advocates, David Ross QC shows how to prepare a case for court. Writing in simple, clear language he gives the benefit of his many years of local and international experience. This second edition features new advice about how to prepare for, and run, an appeal, as well as how to write effective submissions to court. It also describes: • how to hold a court's attention • how to start and stop a witness • how to cross-examine all types of people, from liars to experts • the methods of taking objections to questions • how to address a jury • how to follow etiquette and behave ethically • how to win impossible cases All the principles of advocacy are explained, from the striking start to knowledge of human affairs, and Advocacy is rich with examples taken from real cases.